2023
DOI: 10.1007/s10787-023-01144-w
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive fraction from Plumeria obtusa L. attenuates LPS-induced acute lung injury in mice and inflammation in RAW 264.7 macrophages: LC/QToF-MS and molecular docking

Abstract: In this study, the anti-inflammatory effects of the methanolic extract (TE) of Plumeria obtusa L. (aerial parts) and its fractions were evaluated in vitro, and active fraction was evaluated in vivo. Among tested extracts, dichloromethane fraction (DCM-F) exhibited the strongest inhibition of lipopolysaccharide (LPS)-induced nitric oxide (NO) in RAW 264.7 macrophages. The effect of DCM-F on LPS-induced acute lung injury (ALI) in mice was studied. The animals were divided into five groups (n = 7) randomly; Gp I:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Lotankar et al (2016) showed that the ethanolic extract of P. obtusa markedly reduced the inflammation in carrageenan-induced toxicity in rats [ 53 ]. Another study reported that aerial parts of Plumeria obtusa have anti-inflammatory activity against lipopolysaccharide-induced pneumonia in mice through their ability to decrease the release of inflammatory cytokines [ 12 ]. Boeing et al, proved that plumieride could attenuate ulcerative colitis through its strongest antioxidant and anti-inflammatory effects [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lotankar et al (2016) showed that the ethanolic extract of P. obtusa markedly reduced the inflammation in carrageenan-induced toxicity in rats [ 53 ]. Another study reported that aerial parts of Plumeria obtusa have anti-inflammatory activity against lipopolysaccharide-induced pneumonia in mice through their ability to decrease the release of inflammatory cytokines [ 12 ]. Boeing et al, proved that plumieride could attenuate ulcerative colitis through its strongest antioxidant and anti-inflammatory effects [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that the methanolic extract of the leaves and plumieride-type iridoids isolated thereof demonstrated promising antibacterial activity against multidrug-resistant Gram-negative strains; Klebsiella pneumoniae and Shiga-toxin producing Escherichia coli (STEC) [ 11 ]. According to the results of molecular docking studies, 13- O -coumaroyl plumieride was found to exhibit superior binding affinity for both iNOS and prostaglandin E synthase-1 target receptors and suggest its potential for targeting and modulating the activity of both enzymes [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cytokine family includes chemoattractant chemokines, which are released proteins that control the immune system. 13 Cytokines are produced and secreted by a wide range of cells, including immune cells such as macrophages, T and B lymphocytes, mast cells, fibroblasts, endothelial cells, and other stromal cells. 14 In a signal induction cascade, numerous genes and the transcription factors that regulate them may be activated or inhibited, leading to the generation of further cytokines.…”
Section: Introductionmentioning
confidence: 99%